Hajj Financial Investment in Indonesia: Concept, Policy, and Risk Management of BPKH - Azzam, Hilmy Abdullah (Halal Tourism and Pilgrimage, 2025)
Hajj financial management is a strategic issue in the Islamic public financial system, considering the large amount of funds collected from millions of prospective pilgrims every year. In Indonesia, the management task is carried out by the Hajj Financial Management Agency (BPKH-Badan Pengelola Keuangan Haji) as mandated by Law Number 34 of 2014. This article aims to summarize and analyze the concepts, policies, investment instruments, and risk management of hajj financial investment as explained in the book What & How to Investment Hajj Finance – BPKH (2020). The method used is a literature study with a descriptive-analytical approach. The results of the study show that Hajj financial investment is not only oriented towards achieving returns, but also emphasizes the principles of prudence, sharia compliance, protection of pilgrims' funds, and the creation of value benefits for the benefit of the people. BPKH implements diversification of investment instruments, layered governance, and a structured risk management system to maintain the sustainability of hajj funds. This article is expected to enrich the literature on the management of hajj funds and become a reference for the development of Islamic social finance policies in Indonesia and other Muslim countries.